Photocatalytic asymmetric C-C coupling for CO2 reduction on dynamically reconstructed Ruδ+-O/Ru0-O sites - Hongguang Zhang; Asfaw Yohannes; Heng Zhao; Zheng Li; Yejun Xiao; Xi Cheng; Hui Wang; Zhangkang Li; Samira Siahrostami; Md Golam Kibria; Jinguang Hu (Nature Communications)
Abstract Solar-driven CO2 reduction to value-added C2 chemicals is thermodynamically challenging due to multiple complicated steps. The design of active sites and structures for photocatalysts is necessary to improve solar energy efficiency. In this work, atomically dispersed Ru-O sites in RuxIn2-xO3 are constructed by interior lattice anchoring of Ru. This results in the dynamic reconstruction of Ruδ+-O/Ru0-O sites upon photoexcitation, which facilitates the CO2 activation, *CO intermediates adsorption, and C-C coupling as demonstrated by varied in situ techniques. A SiO2 core in RuxIn2-xO3/SiO2 construction further enhances the solar energy utilization and individual RuxIn2-xO3 nanocrystals dispersion for photocatalytic CO2 reduction reaction. It results in the maximum ethanol production rate up to 31.6 μmol/g/h with over 90% selectivity. DFT simulation reveals that the C2 dimer formation primarily underwent an asymmetric *CO-*CHO coupling route via a low-energy precedence ladder of *CHO. This work provides an insightful understanding of active sites with dynamic reconstruction towards asymmetric C-C coupling for CO2RR at the atomic scale.